Genomes and secondary metabolomes of Streptomyces spp. isolated from Leontopodium nivale ssp. alpinum - Malfent, Fabian; Zehl, Martin; Kirkegaard, Rasmus H.; Oberhofer, Martina; Zotchev, Sergey B. (Frontiers in Microbiology, 2024)
Bacterial endophytes dwelling in medicinal plants represent an as yet underexplored source of bioactive natural products with the potential to be developed into drugs against various human diseases. For the first time, several Streptomyces spp. were isolated from the rare and endangered traditional medicinal plant Leontopodium nivale ssp. alpinum, also known as Edelweiss. In the search for novel natural products, 9 endophytic Streptomyces spp. from Edelweiss were investigated via genome sequencing and analysis, followed by fermentation in different media and investigation of secondary metabolomes. A total of 214 secondary metabolite biosynthetic gene clusters (BGCs), of which 35 are presumably unique, were identified by the bioinformatics tool antiSMASH in the genomes of these isolates. LC-MS analyses of the secondary metabolomes of these isolates revealed their potential to produce both known and presumably novel secondary metabolites, whereby most of the identified molecules could be linked to their cognate BGCs. This work sets the stage for further investigation of endophytic streptomycetes from Edelweiss aimed at the discovery and characterization of novel bioactive natural products.